A study of the elements of depression in "All The Bright Places" (2015) / Zaireen Zuleiqha Zainol Abidin and Mohd Syuhaidi Abu Bakar - Zainol Abidin, Zaireen Zuleiqha; Abu Bakar, Mohd Syuhaidi (2020)
The majority of research that exists on mental illness refers to the portrayals of adults with mental illness in films and television shows but limited research has been conducted on the portrayals of teenagers suffering from mental illness through a medium such as young adult literature. This study discussed and discovered the elements of depression behaviors depicted in the novel -All the Bright Places‖ by Jennifer Niven (2015). The writers chose to study the two main characters, Theodore Finch and Violet Markey, and explored the elements of depression behaviors in the novel. Each text was descriptively examined using textual analysis and coded using a coding book. It was found that the novel depicts all elements of cognitive distortions in Beck's Cognitive Theory of Depression (All-Or-Nothing Thinking, Overgeneralization, Magnification and Minimizing, Personalizing, Mental Filter, Jumping to Conclusions, Labelling, Emotional Reasoning, Mind Reading; and Disqualifying the Positive). To conclude, Niven has addresses not only depression and also suicide with a seriousness and realism. A beautiful juxtaposition. Despite the ending, she leaves the reader with a sense of hope, that it will get better although never easier.